Assessing knowledge management and time performance of building construction projects in Ghana - Francis Gyimah; Kheni Nongiba Alkanam; Elijah Kusi; Fredrick Simpeh (Journal of Construction Project Management and Innovation)
The construction industry, given its nature of frequent disbanding and exit of professionals and workforce after a project is completed, cannot downplay the importance of managing knowledge and the need to manage the knowledge of construction professionals and the workforce at the corporate and project levels. This study sought to assess project knowledge management and time performance of building construction projects in Ghana. The objectives of the study were to determine whether project knowledge managed on past projects is applied on current projects, to determine the impact of project knowledge management on project time performance, and to determine the critical factors governing the application of knowledge management in enhancing project time performance. The study adopted a cross-sectional survey research design with construction professionals employed by 19 D1K1 construction companies within the Greater Accra Region of Ghana as the population. A purposive sampling method was adopted for the study, with a questionnaire as the data collection instrument. The questionnaire was administered by Google Forms, and a response rate of 69% was achieved. The study found that Ghanaian building construction firms apply knowledge gained from previous projects to current projects during construction, and the application of this knowledge managed on current projects during construction explains a 30% improvement in project time performance. Also, the findings of the study suggest improved project supervision and site management, a fully utilised construction team, and proper planning of works, among others, are critical factors that govern the application of project knowledge management for improving project time performance. These factors should be documented and applied as lessons learned on future projects to rid projects of delays and time overruns. The study would enable construction project managers to understand the extent of importance the application of project knowledge management is to a project's time performance. It will also inform construction project managers about the critical factors that the application of project knowledge management improves to enhance project time performance.